Improving education convicts as means of corrections - Shabal, Uladzimir (Journal of the Belarusian State University. Law, 2019)
Administering to the subject of research – education as a means of correcting persons sentenced to imprisonment. The aim of the study is to identify promising ways to develop educational organization sentenced to imprisonment. The main part is justified that the expansion of the practice of distance education in the execution of sentences of imprisonment will contribute to the correction of convicts. Furthermore to these goals, it is necessary to open centers of learning in every institution with an establishment of a particular specialization. Implementation of the opening of centers of education projects with the organization of training on a paid basis will both increase the motivation of the inmates in the conscientious attitude to study and reduce the financial cost of its organization. Require inspectors to employment and living conditions, and psychologists to study the educational level of prisoners and to carry out the administration of prisons interaction with educational institutions in the framework of the developed educational programs will significantly enhance the effectiveness of education as a means of correction in order to follow resocialization. The results can be used in the educational process of educational institutions providing higher education in law.
Keywords: means of correcting the convicts; education condemned to imprisonment; distance learning; education centers